Utility and Role of Abdominal Ultrasonography in the Initial Assessment of Patients with Blunt Abdominal Trauma - SAEEDA KHAN GUL SHARIF GULAB NOOR, NAEEM MUMTAZ (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate the efficacy and utility of abdominal ultrasonography in the initial assessment of patients with blunt abdominal trauma. Methodology: this prospective observational study was done in the surgical department of Lady Reading Hospital, Peshawar. Study duration was one year. All those patients above 13 years of age, who presented to the emergency department with bunt abdominal trauma and who were haemodynamically stable were subjected to intra departmental abdominal sonography by an experienced operator. Findings like presence of free fluid in the peritoneal cavity and indications of other injuries were taken into account. All such patients later underwent emergency laparotomy. Findings at laparotomy were recorded and compared with findings of abdominal ultrasonography. Sensitivity and specificity as well as positive and negative predictive values of abdominal sonography were obtained and a conclusion drawn. Results: a total of 80 patients were included in the study. Male to female ratio was 6.2:1. The most common age group affected was 31-40 years. Road traffic accidents were found to be the most common mode of blunt abdominal trauma, present in 39 (48.75%) cases. Abdominal ultrasonography was performed in all patients. Free fluid/ Haemoperitoneum was detected in 36 (45%) patients while injury to solid organs like liver, spleen and kidneys was documented in 18 (22.5%) patients. All patients underwent emergency exploratory laparotomy where haemoperitoneum was found in 42 (52.5%) cases, while solid organ injuries were encountered in 41 (51.25%) patients. In 7 (8.75) patients, no intra-abdominal injury was found. US was found to have sensitivity of 85.7% and specificity of 100% for free intra-peritoneal fluid. While its sensitivity for solid organ injuries was 43.9% with specificity of 100%. Conclusions: Abdominal sonography in experienced hands can prove to be a useful tool in the assessment of patients with blunt abdominal trauma especially when other modalities like CT are either not available or cannot be performed.